Therapeutic Hydrogel Lenses and the Antibacterial and Antibiotic Drugs Release - Alessandra Pulliero; Aldo Profumo; Camillo Rosano; Alberto Izzotti; Sergio Claudio Saccà (Applied Sciences, 2021)
The aim of this research was to evaluate the effects of different lens types on the availability and efficacy of anti-inflammatory and antibiotic drugs. Three lens types were examined: (1) nonionic hydrogel lenses; (2) ionic hydrogel lenses; and (3) silicone hydrogel lenses. The lenses were incubated with (a) dexamethasone; (b) betamethasone; (c) bromophenacyl bromide; and (d) chloramphenicol. Drug availability was quantified by gradient HPLC, and chloramphenicol antibacterial activity was quantified by testing the inhibition of Salmonella typhimurium growth on agar. The lens allowing the most abundant passage of betamethasone was the ionic hydrogel lens, followed by the silicone hydrogel lens and nonionic hydrogel lens. The lens allowing the most abundant passage of dexamethasone was the ionic hydrogel lens, but only at 0.5 h and 1 h. Regarding chloramphenicol, the ionic hydrogel lens and silicone hydrogel lens allowed more abundant passage than the nonionic hydrogel lens. These results highlight the relevance of adapting lenses to anti-inflammatory therapy, thus allowing a personalized medical approach.